2009
DOI: 10.1016/j.rbmo.2009.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Use of aromatase inhibitors in poor-responder patients receiving GnRH antagonist protocols

Abstract: The efficacy of aromatase inhibitors incorporated in the ovarian stimulation protocols of poor-responder patients undergoing intracytoplasmic sperm injection-embryo transfer cycles was investigated. A total of 70 poor-responder patients were randomized into two groups on day 3 of their menstrual cycle. In Group A, an aromatase inhibitor (letrozole, 5 mg/day) was administered along with a fixed dosage (450 IU/day) of recombinant FSH (rFSH), whereas Group B were treated with the same rFSH dosage alone. A flexibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
76
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 25 publications
4
76
0
2
Order By: Relevance
“…This was consistent with an earlier report that compared a high dose gonadotropin agonist protocol with low dose LZ with gonadotropin in a small number of poor responders and found cost saving effects with the use of LZ, but with no differences in cycle outcomes [7]. In another prospective trial, in direct comparison with antagonist gonadotropin cycles, the addition of LZ significantly reduced cycle cancellation rates due to poor responses and total gonadotropin utilization reduced overall costs [8]. A small meta-analysis however could not demonstrate the superiority of LZ addition over gonadotropins alone [19].…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…This was consistent with an earlier report that compared a high dose gonadotropin agonist protocol with low dose LZ with gonadotropin in a small number of poor responders and found cost saving effects with the use of LZ, but with no differences in cycle outcomes [7]. In another prospective trial, in direct comparison with antagonist gonadotropin cycles, the addition of LZ significantly reduced cycle cancellation rates due to poor responses and total gonadotropin utilization reduced overall costs [8]. A small meta-analysis however could not demonstrate the superiority of LZ addition over gonadotropins alone [19].…”
Section: Introductionsupporting
confidence: 91%
“…Although the prognosis for these women is guarded, leading some to consider other options such as egg donation or adoption, various adjunctive measures have been suggested to improve the ovarian response to gonadotropins. Since there is little evidence to support gonadotropin doses over 450-600 IU/day [1], current approaches have included the addition of oral agents such as clomiphene citrate [2,3] or letrazole [4][5][6][7][8][9], the administration of GnRH antagonists instead of agonists [10][11][12], microdose GnRH agonist "flare" [6,13] and other agents such as growth hormone (GH) [14] and most recently the suggestion that DHEA may be helpful [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further trials used simultaneous regimen of letrozole and gonadotrophins in a GnRH antagonist protocol. 16,17,18 One observational study revealed a better implantation rate with a more favourable follicular fluid hormonal profile, 19 and one RCT confirmed the use of lower dosage of gonadotrophins and lower cancellation rate owing to poor response. 20 Recently improvements in IVF embryology with better fertilization rates and embryo quality mean that fewer oocytes are required by the laboratory.…”
mentioning
confidence: 96%
“…Результаты такого применения этих препаратов в про-граммах ВРТ противоречивы [26, 49,[51][52][53]. В большинстве исследований было показано,…”
unclassified